2005
DOI: 10.2225/vol8-issue3-fulltext-10
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of chromium (VI) from aqueous solutions by the husk of Bengal gram (Cicer arientinum)

Abstract: The potential to remove Cr (VI) from aqueous solutions through biosorption using the husk of Bengal gram (Cicer arientinum), was investigated in batch experiments. The results showed removal of 99.9% of chromium in the 10 mgl -1 chromium solution, the biomass required at saturation was 1 g mg -1 . Kinetic experiments revealed that the dilute chromium solutions reached equilibrium within 180 min. The biosorptive capacity of the (bgh) was dependent on the pH of the chromium solution, with pH 2 being optimal. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
185
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(208 citation statements)
references
References 10 publications
10
185
0
4
Order By: Relevance
“…4, although an increase in Cr (VI) concentration had no drastic effect on removal efficiency (40.32±6.93 vs. 37.41±6.93), higher adsorption yields were observed at lower concentration of metal ions. Similar trend has been reported by other researchers (Chand et al, 1994;Kacer et al, 2002;Ahalya et al, 2005;Tirgar et al, 2006b ).…”
Section: Effect Of Air Pollution Concentrationsupporting
confidence: 91%
See 1 more Smart Citation
“…4, although an increase in Cr (VI) concentration had no drastic effect on removal efficiency (40.32±6.93 vs. 37.41±6.93), higher adsorption yields were observed at lower concentration of metal ions. Similar trend has been reported by other researchers (Chand et al, 1994;Kacer et al, 2002;Ahalya et al, 2005;Tirgar et al, 2006b ).…”
Section: Effect Of Air Pollution Concentrationsupporting
confidence: 91%
“…4 and Table 2 show that Cr (VI) uptake decrease with the increase in air velocity, however, there is no statistical significant difference between Cr (VI) uptake at 1.12 and 2.24 m/s (P>0.05). Consequently, it can be concluded that, however agitation facilitates a proper contact between the metal ions in solution and biomass binding sites and thereby it promotes effective transfer of sorbate ions to the sorbent sites (Ahalya et al, 2005), higher air velocity leads to reduction of contact time (passing faster through sorbent medium) and less adsorption.…”
Section: Effect Of Air Velocitymentioning
confidence: 99%
“…The WHO permissible limit of Cu(II) for drinking water is 2 mg L -1 and that for wastewater and industrial effluents is 3 mg L -1 . Several remediation methods like chemical precipitation, lime coagulation, reverse osmosis, ion exchange and solvent extraction have been developed and used but they either are ineffective or expensive (Ahalya et al 2003). Heavy metal removal processes should be simple, effective and inexpensive.…”
Section: Introductionmentioning
confidence: 99%
“…At lower concentrations, all metal ions present in the solution would interact with the binding sites and thus facilitate maximum adsorption. At higher concentrations, more ions are left unabsorbed in solution due to saturation of binding sites (Ahalya et al, 2005).…”
Section: Bio-treatment By Compound I and Compound Ii Of Saline Wastewatermentioning
confidence: 99%